1968
DOI: 10.1192/bjp.114.509.423
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Psychiatric Illness

Abstract: Many investigators have studied the relationship between life events and psychiatric illness to discover whether certain events predispose to some disorders or precipitate them, and to discover the effect of illnesses already in progress on subsequent life events and the effect of events on established illnesses. The validity of such studies depends, among other things, on the selection of suitable controls. For example, if adult patients with depression differ from a group of controls in that they had a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Because previous research has revealed a prevalence of psychiatric illness among victims of sudden death (18,19) and an association of life events and psychiatric status (20,21), it is possible that the association of death of a significant other and sudden death in the present sample is due only to the greater prevalence of psychiatric illness among the cases than among the controls. Accordingly, we repeated the above matched pairs chi square analyses excluding case-control pairs if either member had a history of psychiatric illness.…”
Section: Sudden Death and Recentmentioning
confidence: 64%
See 1 more Smart Citation
“…Because previous research has revealed a prevalence of psychiatric illness among victims of sudden death (18,19) and an association of life events and psychiatric status (20,21), it is possible that the association of death of a significant other and sudden death in the present sample is due only to the greater prevalence of psychiatric illness among the cases than among the controls. Accordingly, we repeated the above matched pairs chi square analyses excluding case-control pairs if either member had a history of psychiatric illness.…”
Section: Sudden Death and Recentmentioning
confidence: 64%
“…Negative events. Death of a spouse (100); death of a boyfriend (100); divorce (73); death of a close family member (63); jail term (63); recent illness or injury (53); fired at work (47); break up of a family (39); death of a close friend (37); arguments with (25); any change in job status (20); change in church activities (19).…”
Section: Dependent Measuresmentioning
confidence: 99%
“…Significant and positive correlations (r values usually 0.1 to 0.3) have been reported between this measure and bodily symptoms: illnesses of all types (27)(28)(29)(30), severity of myocardial infarctions (28,(31)(32)(33)(34), coronary heart disease (35)(36)(37), the occurrence of depressive types of psychiatric illness (25,26,(38)(39)(40)(41)(42)(43), and other symptoms of psychiatric illness (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). These studies were ably summarized at the two conferences mentioned earlier (1,2).…”
Section: Introductionmentioning
confidence: 96%
“…These factors, in turn, may mean that they show a differential vulnerability to so-called social precipitants. The findings of Morrison and Hudgens who evaluated the influence of a number of life events in affective disorders using hospitalized medical and surgical patients as controls were notable precisely because they failed to turn up striking differences (40,41). Patients classified as having an affective disorder, when compared to the controls, only showed more frequent changes of residence and reported interpersonal discord during the year prior to admission, but this was usually after the disease had become manifest.…”
Section: Problems Associated With Epidemiologic Inquiriesmentioning
confidence: 94%